2016
DOI: 10.1115/1.4032083
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of Five-Axis Milling Configurations and Titanium Alloy Surface Topography

Abstract: Five-axis milling with a ball-end cutter is commonly used to generate a good surface finish on complex parts, such as blades or impellers made of titanium alloy. The five-axis milling cutting process is not straight forward; local cutting conditions depend a lot on the geometrical configuration relating to lead and tilt angles. Furthermore, the surface quality is greatly affected by the cutting conditions that define the milling configuration. This study presents a geometrical model of five-axis milling in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In light of the above, it can be concluded that the analytical methods can be applied to simple tool paths, 24 but in the case of modern tool paths, which consist of freeform curves, geometric simulation cannot be neglected or replaced by other simulation methods in machining process analysis. 25 This is because the interaction of the tool and the workpiece depends on in-process geometry, which is a function of former tool path segments.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the above, it can be concluded that the analytical methods can be applied to simple tool paths, 24 but in the case of modern tool paths, which consist of freeform curves, geometric simulation cannot be neglected or replaced by other simulation methods in machining process analysis. 25 This is because the interaction of the tool and the workpiece depends on in-process geometry, which is a function of former tool path segments.…”
Section: Introductionmentioning
confidence: 99%